2005
DOI: 10.1111/j.1442-2018.2005.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acculturation and social exchange on the expectations of filial piety among Hispanic/Latino parents of adult children

Abstract: This study explores the effects of acculturation and social exchange variables on the expectations of filial piety (values and beliefs about parents' care) among Hispanic/Latino parents of adult children. A convenience sample of 318 Hispanics/Latinos with adult children was assembled in Texas and North Carolina, USA, for face-to-face interviews in order to collect information about their families and to assess their expectations of filial piety by their adult children. The number of years in the USA, age, gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 42 publications
3
32
0
2
Order By: Relevance
“…For example, studies of Dutch elders (Liefbroer and Mulder 2006;de Valk & Schans 2008) found that being female, more educated, and older was related to lower expectations of filial obligation, whereas those from non-Christian religious backgrounds (e.g., Hindus & Muslims) had greater expectations. By contrast, in a sample of Hispanic immigrants in the U.S., Kao and Travis (2005) found that being older, female, and less acculturated was related to increased expectations of filial obligation.…”
Section: Filial Obligation and Preferences For Future Living Arrangemmentioning
confidence: 79%
“…For example, studies of Dutch elders (Liefbroer and Mulder 2006;de Valk & Schans 2008) found that being female, more educated, and older was related to lower expectations of filial obligation, whereas those from non-Christian religious backgrounds (e.g., Hindus & Muslims) had greater expectations. By contrast, in a sample of Hispanic immigrants in the U.S., Kao and Travis (2005) found that being older, female, and less acculturated was related to increased expectations of filial obligation.…”
Section: Filial Obligation and Preferences For Future Living Arrangemmentioning
confidence: 79%
“…However, previous research on variations in expectations of filial obligation among older adults has yielded mixed results. For example, in a sample of Hispanic immigrants in the U.S., Kao and Travis [13] found that being older, female, and less acculturated was related to increased expectations of filial obligation. In contrast, a study of Asian Indian immigrants found no correlations between filial obligation expectations and education or length of residence in the US [14].…”
Section: Introductionmentioning
confidence: 99%
“…Mexican Americans agree significantly more often than do Anglo Americans that elders should be cared for within the family (Crist et al ., 2006). This cultural tradition is strained, however, by the fact that the members of the younger generation acculturate more quickly than do their parents, resulting in intergenerational gaps in family values and a decrease in the reserves for elder care (Kao & Travis, 2005). The author assumed that the family values of more acculturated MAs tend to change more, leading to their perception that assisting their elders with medication is more of a hassle than for their less acculturated counterparts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The gender of the elder and the kinship between the dyad significantly affect the care and support that are given to the elder. Women generally have more advantage over men in receiving support exchanges (Miller & Bermudez, 2004), perhaps because women are more invested and skilled in sustaining emotional ties across generations (Kao & Travis, 2005). When the kinship between the dyad is a parent–child relationship, the elder is more inclined to ask for and receive care from his/her children in return (Kao & Travis, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation